Implications of the Common Link Theory in the Study of the Hadith of the Prophet SAW - Anton Sulthoni; Sigit Yasdi; Ali Masrur; Engkos Kosasih; Dadah Dadah (al-Afkar, Journal For Islamic Studies, 2026)
This article discusses the Common Link theory developed by G.H.A. Juynboll in contemporary hadith studies. This theory, which is a development of Joseph Schacht’s ideas, offers a new perspective in hadith studies by questioning the authenticity and transmission mechanisms of hadith, highlighting the role of a central transmitter in the spread of a sanad, who often becomes the starting point in the construction of a narration. Using a literature review approach, this article analyzes the implications of the Common Link theory on the validity of isnads, matn criticism, and the historicity of the Prophet Muhammad’s (SAW) hadith, while also applying the theory to specific hadith to demonstrate its practical application. The analysis shows that the Common Link theory has fundamental implications for conventional understandings of the origins and sources of hadith, leading to a reconceptualization of the transmission process and the period of their emergence. Although this theory has been challenged by Muslim scholars such as M.M. Azami—who advocates traditional methods like muqaranah and mu‘aradah—its contribution to contemporary hadith studies cannot be overlooked in shaping a more critical and interdisciplinary approach to hadith literature. The study’s findings suggest that this theory offers a critical framework for evaluating hadith, especially in the context of historical reconstruction and the detection of ideological motives behind their transmission.